Intestinal Obstruction among Iranian Children - Azar Nickavar (Iran University of Medical Sciences, 2008)
Background and Aim: Intestinal obstruction is one of the important diseases in children that need to be diagnosed and treated appropriately to prevent complications. The present study was conducted to identify the most common causes of intestinal obstruction, age and sex prevalence, complications and associated anomalies in Iranian children.   Materials and Methods: One hundred children aged under 12 years old with manifestation such as vomiting, abdominal pain, no fecal and gas passage and abdominal distention indicative of intestinal obstruction were studied. Different etiologies of obstruction were documented by of radiologic procedures or during surgery. Sixty and three patients were less than 1 month, 27 between 1-12 months and 10 had 1-12 years. Most of the patients (73) were male.   Results: The most common causes were Hirschprung disease, invagination and imperforated anus with relatively equal prevalence. The most common age of hirschprung disease and imperforated anus was in neonatal period. Invagination was more prevalent during infancy. Intestinal perforation occured in 6 patients, mostly in small bowel atresia obstruction. Hirschprung disease and imperforated anus were most common causes of mortality. Associated anomalies were cardiovascular, urologic, genital and gastrointestinal abnormalities, especially in imperforated anus and hirschprung disease.   Conclusion: The results of this study are largely confirming the findings of previous similar studies in other countries.